Dual Liquid Junction Photoelectrochemistry: Part II. Open-Circuit Photovoltage Variations Due to Surface Chemistry, Interfacial Dipoles, and Non-Ohmic Junctions at Back Contacts. Issue 13 (21st August 2019) - Russell, Margaret A.; Kalan, Roghi E.; Pugliese, Anthony J.; Carl, Alexander D.; Masucci, Clare P.; Strandwitz, Nicholas C.; Grimm, Ronald L.
Abstract : Dual-liquid-junction photoelectrochemistry and finite-element computational modeling quantified the effect on open-circuit photovoltage, V oc, of varying barrier heights at the back, traditionally ohmic contact to a semiconductor. Variations in experimental back-contact barrier heights included changes in the redox potential energy of the contacting phase afforded by a series of nonaqueous, metallocene-based redox couples that demonstrate facile, one-electron transfer and dipole-based band edge shifts due changes in the chemical species at the semiconductor surface. Variation in semiconductor surface chemistry included hydrogen-terminated Si(111) as well as methyl-terminated Si(111) that yields a shift in band-edge alignment of ∼0.3 eV relative to hydrogen termination. While methylation of n-Si improves V oc values at rectifying contacts, methylation at an ohmic contact has a deleterious impact on V oc values. We discuss the present experimental and computational results in the context of non-ideal semiconductor contacts.